Versatile Fe-containing hydroxyapatite nanomaterials as efficient substrates for lead ions adsorption - Mercado Castro, Donaldo Fabio (2017)
The capability of paramegnetic iron-containing hydroxyapatite (Fe-nAp) and waste bioorganic subtrates templeted iron-containing hydroxyapatite (SBO-Fe-nAp) nanoparticles, as Pb(II) cations adsorbants were investigated and compared to those of synthetic hydroxyapatite (nAp). Surface and bulk characterization techniques as XPS, XRD, electrophoretic mobility, FTIR spectroscopy, DLS, and TEM were used to investigate the adsorption mechanisms involved and ICP-AES to determine Pb(II) concentrations in aqueous solutions. The apatite-based nanoparticles were found to be efficient materials for the irreversible adsorption of Pb(II) ions from aqueous solutions, with maximum adsorption capacity increasing as: hydroxyapatite < waste bioorganic subtrates templeted ironcontaining hydroxyapatite < iron-containing hydroxyapatite. Adsorption capacities of 1500 mg g-1 observed for iron-containing hydroxyapatite, are among the highest reported for Pb(II) adsorption. The high surface to volume ratio, low crystallinity, and the negatively charged surface, strongly favour aqueous Pb(II) adsorption on Fe-containing apatites over the positively charged crystalline hydroxyapatite. The adsorption mechanisms involved depend on the available surface hydroxyl and carboxyl groups as well as on the formation of stable lead-containing hydroxyapatite-like structures. Moreover, bimetal adsorption experiments involving Cu(II) and Pb(II) ions show particular selectivity depending on the surface chemistry of the hydroxyapatite-based adsorbent. While hydroxyapatite is selective towards Pb(II), Fe-containing hydroxyapatite selectivity depends on the relative [Pb]/[Cu] ratio, and waste bioorganic subtrates templeted Fe-containing hydroxyapatite, adsorbs both ions with similar capability.